Enhancing medium voltage electrical network configuration for the golden triangle of Kuala Lumpur Malaysia - Ismail I.M.N.; Razali N.M.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Basic amenities like electricity infrastructure in the city center should be within the class of its own. People who work and live in modern, developed city like Kuala Lumpur expect uninterrupted and high quality of supply. Electricity infrastructure will only be constructed when there is a demand. The demand will later be translated into the electrical network circulation through network configuration. In line with rapid technology change, the existing guidelines may not be sufficient to give the best result especially for highly dense and populated areas. Therefore, various network configurations are explored to further enhance the network reliability and security. It is hoped that the new formulated network configuration will increase the network performance as well as continuously supply high quality of electricity in the urban area. 2013 IEEE.